Melatonin suppresses methamphetamine-triggered endoplasmic reticulum stress in C6 cells glioma cell lines - Tungkum W. (2017)
© 2017, Japanese Society of Toxicology. All rights reserved. Methamphetamine (METH) is a neurotoxic drug that causes brain damage by inducing neuronal and glial cell death together with glial cell hyperactivity-mediated progressive neurodegeneration. Previous studies have shown that METH induced glial cell hyperactivity and death via oxidative stress, the inflammatory response, and endoplasmic reticulum stress (ER stress) mechanisms, and melatonin could reverse these effects. However, the exact mechanism of the protective role of melatonin in METH-mediated ER stress has not been understood. This study investigated the protective effect of melatonin against METH toxicity-mediated ER stress in glial cells. Our study demonstrated that METH increased glial cell toxicity related to METH-induced ER stress by stimulating the unfolded protein response (UPR) to activate the expression of ER stress transducers, including phosphorylated doublestranded RNA-activated protein kinase (PKR)-like ER kinase (p-PERK), activating transcription factor (ATF6), and phosphorylated inositol-requiring enzyme 1 (p-IRE1). Moreover, the expression of binding immunoglobulin protein (Bip), CCAAT/enhancer-binding protein homologous protein (CHOP), caspase- 12, phosphorylated eukaryotic translation initiation factor 2 alpha (p-eIF2α) and spliced X-box-binding protein-1 (XBP-1) mRNA were also increased. Melatonin reduced ER stress induced by METH toxicity by reducing the expression of ER stress response genes and proteins in a concentration-dependent manner. In addition, melatonin promoted the expression of Bip chaperone in a concentration-dependent manner. Taken together, our findings suggest that melatonin can protect against ER stress-induced glial cell death induced by METH.